Disonansi kognitif di era digital: memahami perilaku pengguna dan digital well-being - Muhammad Habib Alwi; Neviyarni (CAUSALITA : Journal of Psychology, 2026)
The rapid development of digital technology has provided numerous benefits, yet it has also generated psychological challenges for users. In the digital context, cognitive dissonance occurs when there is a mismatch between individuals’ beliefs and their digital behaviors, which can potentially undermine digital well-being. This study aims to systematically review the relationship between cognitive dissonance and digital well-being through an analysis of 17 scholarly articles published between 2015 and 2025. A literature review method was employed. The findings indicate that cognitive dissonance emerges in various digital contexts, including unmet technological expectations, information overload, social polarization, and unhealthy patterns of social media use. Cognitive dissonance is shown to be associated with digital well-being through increased levels of stress, anxiety, guilt, and dissatisfaction with digital experiences. Furthermore, coping mechanisms adopted by users, such as selective exposure, avoidance, and rationalization, tend to alleviate short-term psychological tension but may exacerbate digital well-being issues in the long term. This review highlights the importance of a deeper understanding of the role of cognitive dissonance in digital behavior and underscores the need for further research on digital well-being.